Differentiation-dependent photodynamic therapy regulated by porphobilinogen deaminase in B16 melanoma - Ickowicz Schwartz, D (Nature Publishing Group, 2004)
Protoporphyrin IX (PpIX) synthesis by malignant cells is clinically exploited for photodiagnosis and photodynamic therapy following administration of 5-aminolevulinic acid (ALA). The expression and activity of the housekeeping porphobilinogen deaminase (PBGD) was correlated to PpIX synthesis in differentiating B16 melanoma cells. Differentiation was stimulated by two inducers, butyrate and hexamethylene bisacetamide (HMBA), both of which promote the formation of typical melanosomes and melanin, as well as morphological changeover. A marked decrease in total PBGD activity and PpIX synthesis was observed following stimulation by butyrate, while HMBA induced an opposite effect. In contrast, ferrochelatase levels remained unchanged. Photodynamic inactivation of the cells undergoing differentiation was largely dependent on the PpIX accumulation, which was modulated by the two inducers butyrate and HMBA. Fluorescence immunostaining with anti-PBGD antibodies revealed a major PBGD fraction in the nucleus and a minor fraction in the cytosol. This nuclear localisation pattern was confirmed by expression of PBGD fused to green fluorescence protein. We suggest that efficient photodynamic therapy of cancer facilitated by ALA administration can be enhanced using combined therapeutic modalities.